Development of Iron- and Vitamin A-Rich Dim Sum from Gourami (Osphronemus goramy) and Chicken Liver for Women of Reproductive Age - Putri, Adinda Sekar Damar; Aries, Muhammad; Nasution, Zuraidah (Jurnal Gizi dan Pangan, 2023)
This study aims to develop and investigate the nutritional value of gourami dim sum products with chicken liver substitution. The research phase includes formulation and nutrient content analysis. Based on the results, one serving of selected formula of gourami dim sum can provide 6.4% to 7.1% of the energy requirement. The dim sum can be claimed as a low in fat and high in iron and vitamin A product.